Peran Pemerintah Dalam Pengembangan UMKM (Studi Kasus pada UMKM Makanan Olahan Ubi Cilembu di Kabupaten Sumedang) - Farida Hanifah; Salsabilla Putri Nurimani; Moh. Rafi Surya Balebat; Ivan Darmawan (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Sumedang Regency, West Java is a district that has various and unique MSMEs. In this study, the study focused on the Cilembu sweet potato business. In addition to the potential existence of MSMEs (Micro, Small, and Medium Enterprises) in Sumedang Regency, there are still various problems occurring. These problems include limited human resources, limited trading centers, and marketing problems. Therefore, it is necessary to optimize the role of the local government in developing the MSME industry as a driver of the economy in Sumedang Regency—especially the role of Dinas Koperasi, Usaha Kecil Menengah, Perdangangan, dan Perindustrian (Diskopukmpp). Business actors really need local government support for the progress of MSMEs, not just a discourse. The Sumedang Regency Government must play a role in encouraging the growth and development of productive businesses, managing and fostering productive businesses, and creating a conducive environment for productive business actors through appropriate regulations.